Konselor dalam Konseling Kelompok Reality Therapy - Yendi, Frischa Meivilona; Neviyarni, Neviyarni; Karneli, Yeni; Netrawati, Netrawati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
Reality therapy is a system that is focused on current behavior, it is to help counselees face reality and fulfill basic needs without harming themselves or other individuals. In group counseling with the reality therapy approach the most important thing is to foster responsibility and awareness of the counselee. Basically humans are beings who are responsible for their own behavior and fulfillment of their needs. Emphasis on what group members do is the key to reality as a counseling group.